Effect of strategic imperative on technology adoption in academic libraries in Pakistan: A TAM & PLS-SEM analysis - Majid Ali; Chun Lyu; Xin Tian; Chengan Jiang; Li Gang (Acta Psychologica, 2025)
Purpose: In the current technological and innovation era, academic libraries are facing challenges in implementing new technologies to provide secure, efficient, and transparent Technology-Based Services (TBS) and finding innovative solutions to enhance information dissemination. This study investigated the impact of Strategic Imperative (SI) on Technology Adoption Strategy (TAS) within academic libraries in Pakistan, by employing the Technology Acceptance Model (TAM), and proposed a conceptual research model. Methodology: The Study employed a survey-based quantitative research design to investigate the SI effect on TAS and the impact of SI and TAS on Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Adoption Willingness (AW) of technology. A structured online survey was designed based on the proposed conceptual model and distributed among librarians across postgraduate colleges, public and private universities (Pakistan) using a convenience sampling technique. Multicollinearity and Common Method Variance (CMV) Bias were calculated to ensure the robustness, reliability, and validity of the model. 206 valid responses analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) on Smart-PLS (version 4.1.0.3). Findings: The results of the structural model highlight the critical relationship between SI and TAS, PU, PEOU, and AW. The data analysis results confirmed a significant positive impact of SI on TAS, PU, and PEOU. Moreover, TAS has a significant impact on PU and AW but an insignificant impact on PEOU. The PLS results demonstrated that the SI played a crucial role in developing an effective TAS, as well as its usability and usefulness, and its impact on librarians' willingness to adopt technology. R2 and Q2 results established the robustness of the structural model. Furthermore, the findings suggest that institutional support and training programs are essential for librarians to enhance their technical skills, thereby improving the usability and ease of use of new technology, which ultimately can increase their willingness to adopt it. Originality: This study contributes to existing research by exploring the impact of SI and TAS on PU and PEOU in academic libraries, with a particular emphasis on the exceptional geographic location of Pakistan. This study is unique in examining the mediating roles of PEOU and PU in the relationship between SI and TAS. The application of PLS-SEM enhances the methodological rigor and proposed conceptual framework-based research findings, providing actionable insights for policymakers and managers and paving the way for future research.